Economics and cost effectiveness of a rain garden for flood-resistant urban design - D. Rinchumphu; N. Suriyanon; N. Phichetkunbodee; S. Munlikawong; C. Wanitchayapaisit; S. Sitthikankun (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Rapid urbanization negatively affects the hydrologic cycle and makes cities vulnerable to disastrous flash floods. It can additionally cause erosion and water pollution in natural ecosystems. Global climate changes have exacerbated such issues, further upsetting hydrologic patterns. Therefore, many regions have considered the rain garden as green infrastructure, which can help mitigate urban runoff. However, design guidelines and the means of assessing rain garden cost effectiveness in the Global South are limited. Furthermore, as many countries in the Global South experience a tropical climate, design guidelines developed in the temperate Global North may not be directly transferable. The need for more information on design and cost effectiveness can make designers and decision makers hesitate to implement such a new strategy. The main objective of the present study is to create a design approach and simultaneously specify the cost of the infiltration rate of the rain garden in urban areas.METHODS: This study focuses on the ability of rain garden design to determine accurately the cost of materials used for construction. Sand and gravel are used in different sand ratios in the filter media layer, namely 1:1, 1:2, 1:3, and 1:4. The storage layer uses gravel only and has only one design. The aim is to determine the change in infiltration rate with an increase in the amount of sand. Knowing the amount of sand can determine the cost per infiltration rate.FINDINGS: The results showed that the most efficient design was a rain garden with a soil:sand ratio of 1:4, which increased the infiltration rate per cost by 2.00 millimeters per hour per United States Dollar per square meter. The lowest efficiency option was a soil:sand ratio of 1:1, which increased the infiltration rate per cost by 1.33 millimeters per hour per United States Dollar per square meter.CONCLUSION: This study will serve as a guide for designers to design a rain garden area according to the needs of the area, having determined the construction cost per infiltration rate. However, spatial requirements, construction costs, and social factors may influence future decisions on rain garden design and must be studied further.